Reassessment of the distribution and population size of Spizella wortheni - Scott Morales, Laura Magdalena; Vela Coiffier, Martha Patricia; Cotera Correa, Mauricio; Almejo Ramos, Mirna; Canales Delgadillo, Julio César (Cambridge University Press., 2018)
Information deficit constrains our capacity to assess the status of threatened species in regional and global contexts. In this study of the endangered Worthen’s Sparrow Spizella wortheni, we first review its current and potential distribution using the species distribution software, Maxent. An initial basic model was constructed using historical records, and used to guide a subsequent search for additional populations in summer 2013. Using the information gathered from our survey, we built a second, breeding model, to update the current and potential species distribution. Population size was estimated using line transects of variable length to count singing males and calculate densities per 10 ha. We found 10 new small reproductive populations dispersed south of the established core area, increasing the extent of occurrence of the species from 25 km2 to almost 17,000 km2. Suitable habitat across the species’ range was more than threefold higher in the breeding compared with the basic model. We counted 316 males, with a mean density of four individuals per 10 ha. Our results demonstrate that conservation assessment based on limited records can exaggerate the vulnerability of species, and confirm that the Worthen’s Sparrow population and geographic distribution range are larger than previously determined, indicating that the Red List status of this species should be reconsidered. The use of niche models was successful in enhancing species information data quantity (e.g. range extensions) and quality (e.g. more precise habitat requirements), facilitating improved understanding of needs and conservation status in the wild.